Chlorophytum sikkimense (Agavoideae; Asparagaceae): a new species from Sikkim Himalaya - Rai, Pramod (Phytotaxa, 2022)
A new species of Chlorophytum is described from Sikkim. The new species is distinct from other closely related species (C. assamicum and C. breviscapum) by its scape with sterile bracts, pedicel articulation above middle, longitudinal anther dehiscence and white ovary. It grows in similar habitat as aforementioned species i.e., floor of tropical mixed deciduous forest at an elevation of 600–700 m and currently known only from Sirisay forest of Sikkim Himalaya. Detailed description and color plates of the new species are provided.